Electronic platforms and transparency in public procurement - Ferreira, I. (2018)
Public procurement represents the largest component of public expenditures and, for that reason, is one of the most sensitive areas of the risk of corruption. There are several governmental investments in this area to accomplish the principle of integrity and to achieve more transparency. In Portugal, in the e-government context, the strategy was the adoption of electronic platforms for procurement, as the main reinforcement measure of transparency in public procurement. Through an exploratory literature review, based on OCDE recommendations and European Union official reports, this paper aims at contributing to the discussion on the use of information and communication technology, specifically electronic platforms, in Portuguese public procurement. While the gains are potentially significant, it should be noted that the implementation of the principle of integrity implies articulated measures of technological and political dimension as well as organizational culture. © 2017 International Business Information Management Association, IBIMA. All rights reserved.